Optimalisasi Program Penurunan Stunting Di Desa Nagrak, Kec. Buahdua, Kab. Sumedang - Azkia, Naya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
Stunting is a serious nutritional problem and must be faced by Indonesia and other countries. Stunting itself is a disorder of child growth and development where the height of stunted children is shorter than that of children of the same age. This study was conducted to find out whether the stunting reduction program in Nagrak Village is optimal or not. To find out, the researcher used a descriptive qualitative research method. In this study, the researcher collected data by documentation, interview, and observation techniques. In an effort to reduce stunting in Nagrak Village, the focus is on three target groups, namely, adolescents, pregnant women and toddlers 0-59 months. The results of the study show that early detection of nutritional problems in Nagrak Village has been carried out with the existence of a youth posyandu program and also the provision of Blood Supplement Tablets (BST) and anemia checks to schools. In addition, in the target group of pregnant women, assistance has been provided regarding the consumption of nutrition and BST or other supplements and additional nutritional intake has been provided for high-risk pregnant women. Stunting treatment for toddlers 0-59 months is carried out with the posyandu program, where the weight and height of toddlers are measured every month so that their growth and development can be monitored, in addition to the provision of supplementary food (PMT) for toddlers who are indicated to be stunted so that they can meet additional nutritional intake. It was concluded that the stunting reduction program in Nagrak Village has been carried out optimally.